1999
DOI: 10.1177/146045829900500107
|View full text |Cite
|
Sign up to set email alerts
|

A review of intelligent content-based indexing and browsing of medical images

Abstract: Physicians are beginning to be able to gain access, through the Internet, to the world's collections of multimedia medical information such as MRI (magnetic resonance imaging) and CT (computer tomography) image archives, videos of surgical operations and medical lectures, textual patient records and media annotations. New techniques and tools are needed to represent, index, store and retrieve digital content efficiently across large collections. In this review, we trace the development of visual information sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…From Fig.1, it could be seen that 3 IC is approximate to the original image with its size being quarter of the original, which works as the ICF of the medical image, and the others show some details of the original image. 3 IC is reasonable to be considered as a certain low frequency component of the original image, while the others are the high frequency ones.…”
Section: Ica Modelmentioning
confidence: 97%
“…From Fig.1, it could be seen that 3 IC is approximate to the original image with its size being quarter of the original, which works as the ICF of the medical image, and the others show some details of the original image. 3 IC is reasonable to be considered as a certain low frequency component of the original image, while the others are the high frequency ones.…”
Section: Ica Modelmentioning
confidence: 97%
“…According to Tang et al, different combinations between text and images for input and output might be used [4]. In general, it is easier to make inferences from text to images than from images to text.…”
Section: I/o Characteristicsmentioning
confidence: 99%
“…Although this approach was originally developed for multimedia repositories such as the Word Wide Web, techniques for content-based access to medical image repositories are a subject of high interest in recent research, and remarkable efforts have been reported [3,4,5]. In particular, CBIR for picture archiving and communication systems (PACS) discussed in [6,7,8] can make a significant positive impact to health informatics and health care.…”
Section: Introductionmentioning
confidence: 99%
“…The radiology department of the University Hospitals of Geneva alone produces currently more than 25, 000 images per day, mostly in multi-slice tomographic series. The importance of retrieval of medical images was identified early [8,9,10] and a large number of projects has started to index various kinds of medical images [11]. Not all of the projects are analysing the visual image content, some simply use the accompanying textual information for retrieval [12].…”
Section: Introductionmentioning
confidence: 99%